Sex Differences in the Physiological and Behavioral Effects of Chronic Oral Methylphenidate Treatment in Rats - Robison, Lisa S.; Michaelos, Michalis; Gandhi, Jason; Fricke, Dennis; Miao, Erick; Lam, Chiu-Yim; Mauceri, Anthony; Vitale, Melissa; Lee, Junho; Paeng, Soyeh; Komatsu, David E.; Hadjiargyrou, Michael; et al. (Frontiers in Behavioral Neuroscience, 2017)
Methylphenidate (MP) is a psychostimulant prescribed for Attention Deficit Hyperactivity Disorder. Previously, we developed a dual bottle 8-hour-limited-access-drinking-paradigm for oral MP treatment of rats that mimics the pharmacokinetic profile of treated patients. This study assessed sex differences in response to this treatment. Male and female Sprague Dawley rats were assigned to one of three treatment groups at 4 weeks of age (n=12/group): control (water), low dose (LD) MP, and high dose (HD) MP. Rats drank 4 mg/kg MP (LD) or 30 mg/kg MP (HD) during the first hour, and 10 mg/kg (LD) or 60 mg/kg MP (HD) for the remaining seven hours each day. Throughout 3 months of treatment, rats were monitored for body weight, food intake, and fluid intake; as well as tested for open field behavior, circadian activity, novel object recognition, and social interaction. Chronic MP treated rats exhibited reduced fluid intake during distinct treatment weeks to a greater extent in males, and reduced total fluid intake in males only. HD MP treatment decreased body weight in both sexes, while HD MP increased total food intake in females only, likely to offset energy deficits resulting from MP-induced hyperactivity. LD and HD MP increased locomotor activity in the open field, particularly in females and during later treatment weeks. MP dose-dependently increased activity during the dark cycle of circadian testing in females, while in males hyperactivity was only exhibited by HD rats. HD MP increased center activity to a greater extent in males, while MP increased rearing behavior in females only. MP had no effect on social behavior or novel object recognition in either sex. This study concludes that chronic oral MP treatment at clinically-relevant dosages has significant effects on food intake, body weight, open field behavior, and wake cycle activity. Particularly marked sex differences were apparent for locomotor activity, with females being significantly more sensitive to the hyperactivating effects of the drug. These findings suggest that chronic MP exposure beginning in adolescence can have significant behavioral effects that are both dose- and sex-dependent, and raise concerns regarding the reversibility of these effects post-discontinuation of treatment.